A new strategy for taste masking of azithromycin antibiotic: development, characterization, and evaluation of azithromycin titanium nanohybrid for masking of bitter taste using physisorption and panel testing studies - Amin F; Khan S; Shah SMH; Rahim H; Hussain Z; Sohail M; Ullah R; Alsaid MS; Shahat AA (Dove Medical Press, 2018)
Fazli Amin,1 Shahzeb Khan,1,2 Syed Muhammad Hassan Shah,3 Haroon Rahim,3 Zahid Hussain,4 Muhammad Sohail,5 Riaz Ullah,6,7 Mansour S Alsaid,6 Abdelaaty A Shahat6,8 1Department of Pharmacy, University of Malakand, Khyber Pakhtunkhwa, Pakistan; 2Department of Pharmaceutical Sciences, School of Health Sciences, University of KwaZulu Natal, Westville 4000, Durban South Africa; 3Department of Pharmacy, Sarhad University of Science and Information Technology, Peshawar, Khyber Pakhtunkhwa, Pakistan; 4Faculty of Pharmacy, Department of Pharmaceutics, Universiti Teknologi MARA, Selangor, Malaysia; 5Department of Pharmacy, COMSATS, Abbottabad, Khyber Pakhtunkhwa, Pakistan; 6Medicinal, Aromatic & Poisonous Plants Research Center (MAPPRC), College of Pharmacy, King Saud University, Riyadh 11451, Saudi Arabia; 7Department of Chemistry, Government College Ara Khel FR, Kohat, Khyber Pakhtunkhwa, Pakistan; 8Phytochemistry Department, National Research Centre, Dokki, Giza, Egypt Background: The obnoxious bitter taste of orally taken antibiotics is one of the biggest problems in the treatment of children. The pediatric population cannot tolerate the bitter taste of drugs and vomit out which ultimately leads to suboptimal therapeutic value, grimace and mental stress so it is the challenging task for the formulation scientists to formulate a palatable formulation particularly to overcome address the issue. Purpose of study: The study aimed to mask and evaluate the unpleasant bitter taste of azithromycin (AZ) in the dry suspension dosage form by physisorption technique. Materials and methods: AZ was selected as an adsorbent and titanium dioxide nanoparticles as adsorbate. The AZ nanohybrids (AZN) were prepared by treating fixed amount of adsorbent with a varied amount of adsorbate, prepared separately by dispersing it in an aqueous medium. The mixture was sonicated, stirred followed by filtration and drying. The AZN produced were characterized by various techniques including scanning electron microscopy (SEM), energy dispersive X-rays (EDX), powder X-ray diffraction (PXRD), HPLC and Fourier-transformed infrared (FTIR). The optimized nanohybrid was blended with other excipients to get stable and taste masked dry suspension dosage form.Results: The results confirmed the adsorption of titanium dioxide nanoparticles on the surface of AZ. The fabricated optimized formulation was subjected for taste masking by panel testing and accelerated stability studies. The results showed a remarkable improvement in bitter taste masking, inhibiting throat bite without affecting the dissolution rate. The product showed an excellent stability both in dry and reconstituted suspension. The optimized formulation of AZN and was found stable when subjected to physical and chemical stability studies, this is because of short and single step process which interns limits the exposure of the product to various environmental factors that could potentially affect the stability of the product. The dissolution rate of the optimized formulation of AZN was compared with its marketed counterpart, showing the same dissolution rate compared to its marketed formulation.Conclusion: The current study concludes that, by fabricating AZ-titanium nanohybrids using physisorption can effectively mask the bitter taste of the drug. The palatability and stability of azithromycin formulation was potentially enhanced without affecting its dissolution rate. Keywords: azithromycin, AZ, titanium dioxide nanoparticles, TNPs, azithromycin–TiO2 nanohybrid, AZN, dissolution, physisorption